CHALLENGES AND SOLUTIONS IN INTENSIVE LANGUAGE TEACHING - Safarova Dildora; Qo'chqorova Muxlisa; Keldiyorova Iroda (TADQIQOTLAR, 2025)
Annotation Intensive language teaching programs aim to accelerate language acquisition in a condensed timeframe, often requiring high learner motivation, consistent practice, and effective teaching strategies. However, these programs come with unique challenges such as learner fatigue, curriculum overload, and limited individual attention. This article explores common problems faced in intensive language environments and proposes practical solutions, such as differentiated instruction, integration of technology, and psychological support. Understanding these challenges is essential for improving learning outcomes and ensuring student well-being in intensive settings.